SCIENCE TECHNOPARK: PUSAT HILIRISASI RISET LAHAN BASAH - Muhammad Rizwandi; Bani Noor Muchamad; Naimatul Aufa (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Science Technopark is one of the strategies employed by the Indonesian government to face the challenges of the industrial revolution 4.0 and 5.0. Science Technoparks are commonly found in the regions of Java and Sumatra. Therefore, a Science Technopark in Kalimantan, particularly South Kalimantan, is highly needed for equitable development. Moreover, this region has a prominent commodity that must be preserved—wetlands. However, the potential of these wetlands has not been fully optimized, and their existence is starting to be threatened. The Science Technopark is proposed as a solution for the downstreaming of wetland research while also developing the potential of the wetlands and anticipating ecosystem damage. Therefore, the design of the Science Technopark: Center for Wetland Research Downstreaming aims to optimize the potential and preserve the existence of the wetlands. This design adopts the positive analogy method to merge nature and technology into one harmony, with the concept of "eco-tech architecture" as a solution to its architectural challenges. Through this concept, an architecture is realized that harmonizes technology with the wetland ecosystem, ensuring the sustainability of its existence and environmental potential.